Exploring the Impact of Job Rotation on Organizational Performance: A Qualitative Inquiry within the Yobe State Civil Service - Cheri, Lawan; Kaku, Mohammed; Goni, Umar Mohammed; Aliyu, Aliyu Sabo (Kashere Journal of Politics and International Relations, 2025)
This study examines the perceptions and effects of job rotation on civil servants within the Yobe State Civil Service, with a focus on its impact on employee commitment and productivity. Using a qualitative research design, data were collected through interviews and focus groups, and subjected to a thematic analysis. The findings reveal a duality of perceptions among civil servants: while the theoretical benefits of job rotation, such as skill diversification, knowledge acquisition, and the reduction of corruption, are widely acknowledged, the practical implementation of job rotation is viewed as a significant source of frustration. Key findings indicate that the current arbitrary and unstructured nature of transfers negatively affects both employee commitment and productivity. Participants expressed concerns over the inability to master a skill, leading to a "jack of all, master of none" effect, and cited instances of operational disruption caused by mid-task transfers. Consequently, the research suggests that resistance to change is primarily a result of a flawed implementation rather than the concept of job rotation itself. The study concludes with practical recommendations for the Yobe State Civil Service, advocating for a shift from the current arbitrary system to a structured, transparent, and predictable rotation policy to effectively harness the program’s potential for developing a more versatile and committed workforce.